Transient diplopia in dental outpatient clinic: An uncommon iatrogenic event - Balaji S (Wolters Kluwer Medknow Publications, 2010)
A healthy 32-year-old female patient required an extraction of the right maxillary third molar. Lidocaine containing 1:80,000 epinephrine for right posterior superior alveolar nerve block was administered in the mucobuccal fold above the third molar to be extracted at our hospital. After few minutes of posterior superior alveolar block anesthesia, patient felt double vision. The condition was subsequently diagnosed as transient diplopia due to temporary paralysis of lateral rectus muscle due to involvement of the VI cranial nerve. The patient recovered in 30 minutes and the treatment was performed successfully. This article discusses the possible scientific explanation for this phenomenon.